Synthesis of α-Phenyl β-Enamino γ-Sultims: the New Horizon of the CSIC Reaction - Chuchvera, Yaroslav O.; Tararina, Valentyna; Chuchvera, Inna; Ostapchuk, Eugeniy N.; Popova, Maria V.; Shishkina, Svitlana V.; Volovenko, Yulian M.; Dobrydnev, Alexey V. (Synlett, 2024)
Herein, we report the novel strategy for the synthesis of 4-enamino-5-phenyl-2,3-dihydroisothiazole 1-oxides (in other words α-phenyl β-enamino γ-sultims) based on the CSIC reaction. Particularly, readily available α-amino nitriles (the Strecker products) reacted with benzyl sulfinyl chloride to give the corresponding sulfinamides, which upon treatment with excess of LiHMDS converted into the target α-phenyl β-enamino γ-sultims. The method works well and tolerates strained 3- and 4-membered spirocyclic substituents. A preliminary in silico study indicated that the γ-sultim scaffold can be considered a promising pharmacophore template.
Keywords: sulfinamides; enamines; sultims; CSIC reaction; cyclization